PENGARUH MOTIVASI KERJA TERHADAP KINERJA POLISI PADA SATUAN LALU LINTAS KEPOLISIAN RESOR PASER - Dedy Darmawan; Ahmad Rifai (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2024)
This study aims to determine the influence of work motivation, which includes the need for achievement, the need for power, and the need for affiliation, both simultaneously and partially, on the performance of police officers in the Traffic Unit of the Paser Police Resort. This is a quantitative study designed to address the formulated research problems, achieve specific objectives, and test hypotheses. The population consisted of all 45 officers in the Intelligence and Security Unit of the Paser Police Resort, and due to the relatively small number, the entire population was used as the sample. Data were analyzed using regression analysis. The results showed that the need for achievement has a positive and significant effect on police performance, as indicated by a t-value greater than the t-table value. The need for power, however, while having a positive relationship, did not significantly influence performance since its t-value was lower than the t-table value. The need for affiliation also showed a positive and significant effect on performance, with a t-value higher than the t-table value. Among the three motivational factors, the need for affiliation was found to be the most dominant variable influencing police performance in the Traffic Unit of the Paser Police Resort.